A French Canadian Adaptation and Validation of the Vividness of Visual Imagery Questionnaire and Plymouth Sensory Imagery Questionnaire. - Landry, Catherine; Lessard, Laurence; Saint-Louis, Jeffrey; Gosselin, Frédéric; Charest, Ian; Taschereau-Dumouchel, Vincent; Vallet, Guillaume T. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2026)
Mental imagery plays a central role in various cognitive processes and is increasingly investigated in cognitive science. Yet standardized tools for its assessment in French-speaking populations remain scarce. This study examined the psychometric properties of two widely used self-report instruments of mental imagery within the French Canadian population: the Vividness of Visual Imagery Questionnaire (VVIQ) and the Plymouth Sensory Imagery Questionnaire (Psi-Q)--here termed VVIQ-Québec (QC) and Psiq-QC. A total of 328 adults completed the VVIQ-QC and Psiq-QC, with a randomly selected subsample (n = 73) repeating the assessment 1 month later. Exploratory factor analysis of the VVIQ-QC (eyes-open) revealed, as in the original VVIQ, distinct factors corresponding to each prompt cluster (i.e., relative, sunrise, landscape, and storefront). The Psiq-QC yielded a six-factor solution after excluding the Body modality, diverging from the original seven-factor model. Both instruments showed strong internal consistency, temporal stability, and convergent validity. No significant effects of age, sex, or education were observed on imagery scores. These findings provide the first validated French Canadian versions of the VVIQ and Psi-Q, available via the Open Science Framework at https://osf.io/wuhja, offering reliable tools for both research and clinical applications.